Business Risks and Performance of SMEs in the Malaysian Construction Sector - SALLEH, FAUZILAH; ROHAIZAD, WAN NUR FATIHAH; ZAIB, NOOR IZYAN SHAFIQA MOHD; KADIMON, NUR SHAHRIN NADIA; SYAHRUDDIN, SYARMIDAH (The journal of contemporary issues in business and government, 2021)
Small and medium-sized enterprises (SMEs), especially their business risks and performance, are the primary economic drivers of the construction sector in Malaysia. Most studies focused on the performance of SMEs, but their business risks were underexplored. With that, the current study aimed to determine the elements of business risks that affect the performance of SMEs in the construction sector within the Malaysian context. For this study, five construction companies in different states were selected as case studies. Financial risk, government regulation, managerial capacity, delay in the project, and technology were identified as the critical elements of business risks that affect the performance of SMEs. Through the emerging new ventures in the business market, the performance of SMEs is undoubtedly one of the vital economic drivers that can boost the country’s economic growth.